The Effect of Environtment Characteristics on Diarrhea Occurrence Among Children Under Five in Palembang (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Diarrhea is still a public health problem in developing countries such as Indonesia because morbidity and mortality rates are still high in these areas. A morbidity survey conducted by the Diarrhea Department of the Ministry of Health in Indonesia between 2000 and 2010 shows rising incidences of diarrhea in children. In 2000, Incidence Rate (IR) diarrhea incidents occurred in 301/1000 members of the population, and this increased to 411/1000 in 2010. Cases of diarrhea have become dangerous when suffered by infants because the mortality rate will increase because weaker immunity than olders. Environmental factors such as water, waste, and toilet contribute greatly to cases of diarrhea; therefore, in this research, we analyze environmental characteristics’ effects on the incidence of diarrhea in infants in Palembang. This study uses a mixed-method design combining quantitative data collection using secondary data from the Department of Health with qualitative data collection using in-depth interviews of Palembang’s local government and health center personnel in the districts with the highest and lowest cases of diarrhea. Quantitative data analysis are visualized in the form of a map, while qualitative data are analyzed using content analysis. The results show that Ilir Timur I has the highest incidences of diarrhea while the Sako district has the lowest. Based on the results of the analysis, Ilir Timur I has more cases of diarrhea largely because of its non-working area health centers. Sako has the fewest cases of diarrhea because the clinics, doctors, and midwives in private practice in the region of Sako do not report the cases, as well as because of factors related to access remote health centers. Therefore, interventions based on health data for diarrhea need to be restyled for a drastic reduction of diarrhea cases.